Tantangan dan Peluang Kontrak Istisna dalam Pembiayaan Perumahan Syariah di Indonesia - Putra, Muhammad Deni; Sururi, Sururi; Akasumbawa, Muhammad Dedat Dingkoroci; Ismail, Dailani; Marlion, Farid Ahmad (Al-Amien Prenduan for Islamic Institute, 2025)
This study aims to examine the application of the Istisna contract in Islamic housing finance in Indonesia, and to identify the challenges and strategic efforts required for its effective implementation. A qualitative approach was employed through a literature review of relevant academic works, regulatory frameworks, and current practices in Islamic finance. The findings reveal that although Istisna holds significant potential as a Sharia-compliant alternative to conventional financing, its implementation faces numerous challenges. These include low public literacy in Islamic finance, inadequate regulatory infrastructure, and cultural resistance to non-conventional financing methods. Developers and consumers also encounter technical and legal obstacles, such as complex contractual arrangements and weak legal protections. Additionally, the lack of effective educational strategies and financial literacy initiatives further slows adoption. The study highlights the need for a multidimensional approach involving the integration of financial technology, regulatory strengthening, collaboration between developers and Islamic financial institutions, and the involvement of community leaders as agents of socialization. To foster the growth of Islamic housing finance based on Istisna, comprehensive policy interventions and institutional capacity building are essential. Contextual strategies that are responsive to local needs and foster synergy among stakeholders can position Istisna not only as a Sharia-compliant financing instrument but also as one that is adaptive to Indonesia’s socio-economic dynamics.